Low-field optically detected EPR spectroscopy of transient photoinduced radical pairs. - Rodgers, C; Henbest, K; Kukura, P; Timmel, C; Hore, P (2005)
The effects of simultaneously applied weak static and weak radio frequency magnetic fields on the recombination of transient (<100 ns) radical pairs have been investigated using a low-field optically detected electron paramagnetic resonance technique. Measurements on the photoinduced electron-transfer reaction of perdeuterated pyrene with 1,3-dicyanobenzene using a approximately 0.3 mT radio frequency field at three separate frequencies (5, 20, and 65 MHz) in the presence of 0-4 mT static fields yield spectra that are strikingly sensitive to the frequency of the time-dependent field, to the strength of the static field, and to the relative orientation of the two fields. The spectra are simulated using a modified form of the gamma-COMPUTE algorithm originally devised for calculating magic angle spinning NMR spectra of polycrystalline samples. The essential features of the spectra are consistent with the radical pair mechanism and were satisfactorily simulated using parameters whose values are either known independently or for which estimates are readily available. The calculations included hyperfine couplings to four deuterons in the pyrene cation radical and three protons in the 1,3-dicyanobenzene anion radical. Spin-selective recombination was modeled using an exponential distribution of radical encounter times. The results are discussed in the context of the proposal that radical pair chemistry forms the basis of the magnetoreceptor that allows birds to sense the Earth's magnetic field as a source of compass information during migration.